2016
DOI: 10.3233/jad-150523
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Small Vessel Disease and Motoric Cognitive Risk Syndrome: Results from the Kerala-Einstein Study

Abstract: Background The contribution of cerebral small vessel disease to cognitive decline, especially in non-Caucasian populations, is not well established. Objective We examined the relationship between cerebral small vessel disease and motoric cognitive risk syndrome (MCR), a recently described pre-dementia syndrome, in Indian seniors. Methods 139 participants (mean age 66.6 ± 5.4 y, 33.1% female) participating in the Kerala-Einstein study in Southern India were examined in a cross-sectional study. The presence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
66
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(74 citation statements)
references
References 42 publications
7
66
1
Order By: Relevance
“…This study also found that BMI was significantly associated with MCR in the French cohort, as demonstrated in previous work [3]. The prevalence of WMH was also consistent with previous studies [14, 22, 24, 3944]. However, the French cohort did have a higher prevalence of WMH overall.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This study also found that BMI was significantly associated with MCR in the French cohort, as demonstrated in previous work [3]. The prevalence of WMH was also consistent with previous studies [14, 22, 24, 3944]. However, the French cohort did have a higher prevalence of WMH overall.…”
Section: Discussionsupporting
confidence: 92%
“…This finding suggests that vascular mechanisms other than WMH may contribute to the pathophysiology of MCR, as was previously suggested in the case of regional lacunar infarcts [14]. Wang et al [14] reported that WMH overall were not associated with MCR and our study replicated these findings. Our study further evaluated this by assessing regional WMH in the context of MCR in two independent cohorts of non-demented older adults.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Alternatively it is plausible that the combination of slow gait and subjective cognitive complaints increases an individual’s risk of falling by reducing their overall ability to compensate for physical impairments with adequate cognitive function or vice versa. Finally, the few studies examining correlates of MCR have reported associations with higher levels of chronic disease, dementia, depression, hypertension, diabetes, obesity, and sedentariness as well as stroke [12, 13, 38], suggesting MCR may be a good marker of overall health. A number of these factors provide potential targets for therapeutic interventions to prevent falls.…”
Section: Discussionmentioning
confidence: 99%